Using Didactive Games in Mother Tongue Lessons - Toxirovna, Turdiyeva Gulbahor (Researchparks Publishing, 2023)
In this article, we will look at some interactive methods that can be used in native language lessons and the benefits they offer. The use of interactive methods in native language lessons greatly improves the language learning process, making it more interesting and interesting for students. Games are a fun way to keep students interested and learning more fun. They can be used to teach vocabulary, grammar and pronunciation, among other things.